OB-STM: An Optimistic Approach for Byzantine Fault Tolerance in Software Transactional Memory - Ribeiro, Tulio Alberton; Lung, Lau Cheuk; Netto, Hylson Vescovi (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2013: Anais do III Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2013)
Recently, researchers have shown an increased interest in concurrency control using distributed Software Transactional Memory (STM). However, there has been little discussion about certain types of fault tolerance, such as Byzantine Fault Tolerance (BFT), for kind of systems. The focus of this paper is on tolerating byzantine faults on optimistic processing of transactions using STM. The result is an algorithm named OB-STM. The processing of a transaction runs with an optimistic approach, benefiting from the high probability of messages being delivered in order when using Reliable Multicast on a local network (LAN). The protocol has a better performs when messages are delivered ordered. In case of a malicious replica or out-of-order messages, the Byzantine protocol is initiated. In smaller scenarios and using an optimistic approach, the protocol has a better throughput than Tazio.